Dharmasūtra parallels : containing the Dharmasūtras of Āpastamba, Gautama, Baudhāyana, and Vasiṣṭha - Olivelle, Patrick; Lariviere, Richard W. (Motilal Banarsidass Publishers, 2005)
Parallel Sanskrit text with English translation of Āpastambadharmasūtra, Gautamadharmasutra, Baudhāyanadharmasūtra, Vāsiṣṭhadharmasūtra and Nāradasmr̥ti; critical edition.